ANALISIS KINERJA PEGAWAI DALAM PELAYANAN PERENCANAAN ANGGARAN PADA BADAN KEUANGAN DAN ASET DAERAH KABUPATEN GORONTALO - Annisa Fitri Gobel; Arifin Tahir; Zuchri Abdussamad (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2023)
This study aims to identify and describe Employee Performance Analysis in Budget Planning Services at the Gorontalo Regency Regional Finance and Asset Board, as well as the factors that determine the success of Employee Performance Analysis in Budget Planning Services at the Gorontalo Regency Regional Financial and Asset Boards seen from the aspect of work quality , punctuality, initiative, ability to work, and communication skills. The approach used is descriptive qualitative with data collection techniques conducting interviews, observation, and documentation. The data analysis method uses the Miles Huberman model, namely through the stages of data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that the analysis of employee performance in budget planning services at the Gorontalo Regency Regional Finance and Asset Board has been going well because of an increase in the quality and capacity of employees, strengthening the role of leadership, and increasing collaboration between parties. In addition, the factors that determine the success of Employee Performance Analysis in Budget Planning Services at the Gorontalo Regency Regional Finance and Asset Board in this case the quality of work, initiative, work ability, and communication skills have been carried out properly. It's just that they have constraints in terms of time because at the time of submitting the budget planning files it is still often done at the end of a very tight time. This is because the finalization of the document must comply with the completeness of the files from all OPDs in Gorontalo district.